Przed Bożym Sądem… Prawo z śmiercią, aniołami i niebem, abo Kazanie o Wniebowzięciu Panny Naświętszej Samuela Brzeżewskiego - Dybek, Dariusz (Tematy i Konteksty, 2016)
Samuel Brzeżewski is a forgotten Polish Baroque preacher. There are three extant sermons by him (published 1640–1645) and a biography of the blessed Michał Giedroyc edited by him. Although the sermons are not popular, they are interesting as they represent the so-called Conceptismo of Polish homiletics. One of the sermons is dedicated to a late nobleman, J. Pucniewski, who is compared to an olive tree. The other two sermons relate to the Blessed Virgin. Zaciąg… deals with the search for the best court for Virgin Mary, which consists of sinners and the suffering. The third one, Prawo z śmiercią, aniołami i niebem… [The trial with death, angels and Heaven, or the sermon of the Assumption of the Virgin] was written in commemoration of the Assumption of the Virgin. It describes the trial between the people and Heaven. The preacher is the prosecutor, the faithful are the witnesses, and God is the ultimate judge. Referring to the Bible, the Antiquity and writers of early Christianity, Brzeżewski created an absorbing, though not flawless, sermon using an unusual concept.